2010
DOI: 10.2175/106143010x12609736966928
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Degradation Products of Erythromycin A Arising from Ozone and Advanced Oxidation Process Treatment

Abstract: The degradation products of the macrolide antibiotic erythromycin A (ERY) arising from direct ozone attack and hydroxyl radical attack are presented for the first time. Ozone treatment was carried out by spiking ozone stock solutions to solutions containing ERY-ERY:O 3 5 1:5 and 1:10 (M:M), while, in parallel, t-BuOH was used as a hydroxyl radical (NOH) scavenger. The advanced oxidation processes (AOPs) O 3 /UV, O 3 /H 2 O 2 , and UV/H 2 O 2 were carried out to recognize and verify possible differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…Similar pattern is observed for ERY (macrolide), which also has been described to affect the resistance of bacterial communities in activated sludge (Li and Zhang, 2010) but, in contrast, not in biofilms at environmental relevant concentrations (Wunder et al, 2013). Because of these problems, different authors have studied an alternative degradation processes for both compounds as well as the generation of any transformation products (Tc (Halling-Sørensen et al, 2002;Parka and Chounga, 2007;Chen and Huang, 2010;Khan et al, 2010) and ERY (Kim et al, 2004a(Kim et al, , 2004bLuiz et al, 2010;Pengelly, 2010)). …”
Section: Introductionmentioning
confidence: 53%
“…Similar pattern is observed for ERY (macrolide), which also has been described to affect the resistance of bacterial communities in activated sludge (Li and Zhang, 2010) but, in contrast, not in biofilms at environmental relevant concentrations (Wunder et al, 2013). Because of these problems, different authors have studied an alternative degradation processes for both compounds as well as the generation of any transformation products (Tc (Halling-Sørensen et al, 2002;Parka and Chounga, 2007;Chen and Huang, 2010;Khan et al, 2010) and ERY (Kim et al, 2004a(Kim et al, , 2004bLuiz et al, 2010;Pengelly, 2010)). …”
Section: Introductionmentioning
confidence: 53%
“…11). Five other oxidation products, which resulted from reaction with HO•, were also identified [55]. Radjenovic et al [56] reported ozonation products of roxithromycin, which mostly involved HO• reactions.…”
Section: Antibioticsmentioning
confidence: 97%
“…A demethylated product also occurs for ozone reactions with erythromycin, which results from direct ozone attack on the tertiary amine group [55] (Fig. 11).…”
Section: Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The water quality deterioration is increasing due to increase discharge of wastewater containing recalcitrant, inhibitory pollutants into the immediate environment (Khan et al 2009;Chong et al 2010). Thus, higher concentrations of these pollutants are expected to be aggravated in the nearest future due to the ever-increasing pollution index (Luiz et al 2010). A study has shown that the variation in the concentration of contaminants detected in water could be ascribed to different consumption pattern across countries (Luiz et al 2011).…”
Section: Introductionmentioning
confidence: 99%